1) 8 - 4(- 7x + 8) = 4
8 + 28x - 32 = 4
28x = 4 - 8 + 32
28x = 28
x = 1
2) 1 - 6(2x - 3) = - 2
1 - 12x + 18 = - 2
- 12x = - 2 - 1 - 18
- 12x = - 21
x = 1,75
3) 10 + 9(- 10 - 9x) = 8 - x
10 - 90 - 81x = 8 - x
- 81x + x = 8 - 10 + 90
- 80x = 88
x = - 1,1
4) - 1 + 8(7 - 6x) = 2x + 6
- 1 + 56 - 48x = 2x + 6
- 48x - 2x = 6 + 1 - 56
- 50x = - 49
x = 0,98
5) - 2 + 3(1 + 2x) = - 2x + 3
- 2 + 3 + 6x = - 2x + 3
6x + 2x = 3 + 2 - 3
8x = 2
x = 0,25
6) - 3x + 4 = - 10 + 5(- 7 - x)
- 3x + 4 = - 10 - 35 - 5x
- 3x + 5x = - 10 - 35 - 4
2x = - 49
x = - 24,5
1; 1,75; -1,1; 0,98; 0,25; 24,5
Объяснение:
1) 8-4(-7x+8)=4
28x-32=-4
28x=28
x=1
2) 1-6(2x-3) =-2
-12x+18=-3
-12x=-21
x=1,75
3) 10+9(-10-9x)=8-x
10-90-81x=8-x
10-90-8=-x+81x
-88=80x
x=-1,1
4) -1+8(7-6x)=2x+6
-1+56-48x=2x+6
-1+56-6=48x+2x
49=50x
x=0,98
5) -2+3(1+2x)=-2x+3
-2+3+6x=-2x+3
-2+3-3=-2x-6x
-2=-8x
x=0,25
6) -3x+4=-10+5(-7-x)
-3x+4=-10-35-5x
-3x+5x=-10-35-4
2x=-49
x=24,5
1) 8 - 4(- 7x + 8) = 4
8 + 28x - 32 = 4
28x = 4 - 8 + 32
28x = 28
x = 1
2) 1 - 6(2x - 3) = - 2
1 - 12x + 18 = - 2
- 12x = - 2 - 1 - 18
- 12x = - 21
x = 1,75
3) 10 + 9(- 10 - 9x) = 8 - x
10 - 90 - 81x = 8 - x
- 81x + x = 8 - 10 + 90
- 80x = 88
x = - 1,1
4) - 1 + 8(7 - 6x) = 2x + 6
- 1 + 56 - 48x = 2x + 6
- 48x - 2x = 6 + 1 - 56
- 50x = - 49
x = 0,98
5) - 2 + 3(1 + 2x) = - 2x + 3
- 2 + 3 + 6x = - 2x + 3
6x + 2x = 3 + 2 - 3
8x = 2
x = 0,25
6) - 3x + 4 = - 10 + 5(- 7 - x)
- 3x + 4 = - 10 - 35 - 5x
- 3x + 5x = - 10 - 35 - 4
2x = - 49
x = - 24,5
1; 1,75; -1,1; 0,98; 0,25; 24,5
Объяснение:
1) 8-4(-7x+8)=4
28x-32=-4
28x=28
x=1
2) 1-6(2x-3) =-2
-12x+18=-3
-12x=-21
x=1,75
3) 10+9(-10-9x)=8-x
10-90-81x=8-x
10-90-8=-x+81x
-88=80x
x=-1,1
4) -1+8(7-6x)=2x+6
-1+56-48x=2x+6
-1+56-6=48x+2x
49=50x
x=0,98
5) -2+3(1+2x)=-2x+3
-2+3+6x=-2x+3
-2+3-3=-2x-6x
-2=-8x
x=0,25
6) -3x+4=-10+5(-7-x)
-3x+4=-10-35-5x
-3x+5x=-10-35-4
2x=-49
x=24,5